Extrovert and Introvert Personality Toward Speaking Achievement; A Comparative Study at SMP Negeri 10 Parepare - Sureda; Ika Yanti Ziska (La Parole : Journal of Language Teaching and Pedagogy, 2020)
Speaking is one way to communicate in which ideas and thought delivered through message orally. To enable students to communicate, we need to apply the language in real communication. Personality plays an important role to improve speaking ability. The characteristic of people which causes consistency of feeling, thinking, and behavior. One aspect that constructs personality is extrovert-introvert. The purpose of this study is to generally try to find out which one of the Extrovert and Introvert students that have the better speaking achievement and to Investigate whether there is a difference between the Extrovert and Introvert students personality in speaking achievement in eighth grade at SMP Negeri 10 Parepare. The method used in this research is quantitative research and Two-Way Analysis of Variance. This research involved only one class of eight grade students in SMP Negeri Parepare. All of the samples are 32 students. This research was done in august in the new semester of the first-grade students in the academic year 2018/2019. In this study, the researcher used a questionnaire to know between extrovert and introvert students. This research is started by collecting theory after that giving the students personality tests to the eighth grade of SMP Negeri 10 Parepare and then classifying the extrovert student and introvert student. Then, after classifying students' personalities, the researcher gave students' speaking scores to design comparing the personality of the two students with their speaking scores. The speaking score of extroverted students was 75.92, on average, where the average introverted student was 71.67. This means that the null hypothesis (H0) is accepted. It can be assumed that there is no significant difference between extroverted and introverted students on the speaking achievement of students, but extroverted students have higher English competency skills because of their natural willingness to speak than introverted students. Sometimes introverted students can match extroverted students with their unique strengths.